2021
DOI: 10.5398/tasj.2021.44.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Sago of Gebang Tree (Corypha utan Lamk) from Different Locations in West Timor - Indonesia for Broilers

Abstract: Two experiments were conducted to evaluate the nutritional value of sago from different locations in West Timor, Indonesia for broilers. Experiment I aimed at determining the apparent metabolizable energy (AME) and nutrient digestibility of sago from different locations. A total of 120 broilers (unsexed, age 21 d) were randomly distributed to 24 metabolic cages (5 birds/cage). The experimental design was a completely randomized design (CRD) consisting of 6 treatments and 4 replications. The experimental diets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 42 publications
3
7
1
Order By: Relevance
“…In this study, a range of 0–97.51 μg/kg (mean 48.76 μg/kg) of ochratoxins was obtained and were comparable to other previous studies globally. Nalle et al 57 reported a mean value of 20.385 μg/kg in corn grains and corn products from different sources in West Timor, Indonesia. Kamala et al 58 reported a range of 16–73 μg/kg OTA concentration in maize samples from Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a range of 0–97.51 μg/kg (mean 48.76 μg/kg) of ochratoxins was obtained and were comparable to other previous studies globally. Nalle et al 57 reported a mean value of 20.385 μg/kg in corn grains and corn products from different sources in West Timor, Indonesia. Kamala et al 58 reported a range of 16–73 μg/kg OTA concentration in maize samples from Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…Gross energy. The gross energy (GE) content of samples was determined using an automatic Bomb Calorimeter (IKA C2000) based on the method described by Nalle et al (2021) as follows: weighed 1 gram of the ground sample and placed in a dish. As many as 10 cm threads were tied to the fuse wire and positioned under the ground sample.…”
Section: Excreta Collection For Ame and Nutrient Digestibility Determ...mentioning
confidence: 99%
“…The neutral detergent fiber (NDF) content of sago was 18.9-26.7% (Nalle et al, 2017(Nalle et al, , 2019; while, the NDF content of rice bran was 61.7%. The phytic acid content of rice bran was 50.5-84.8 g/kg DM (Garcia et al, 2012;Kaur et al, 2011); while in sago was reported 30,61 g/kg (Nalle et al, 2019(Nalle et al, , 2021.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations